Registration of WCL‐LO4‐Gail Lesquerella with Improved Harvest Index. Issue 3 (15th July 2013) - Dierig, David A.; Dahlquist, Gail H.; Coffelt, Terry A.; Ray, Dennis T.; Isbell, Terry A.; Wang, Guangyao
Abstract : WCL‐LO4‐Gail lesquerella ( Physaria fendleri L.) germplasm line (Reg. No. GP‐34, PI 666045) was publicly released jointly by the USDA‐ARS and the University of Arizona, in 2012 as part of the new crops breeding program. The germplasm was developed by mass selection originating from lesquerella germplasm WCL‐LO3. The germplasm has an average oil content of 29% and 44% lesquerolic acid. It has a harvest index of 16.5, a plant biomass of 157 g, and a seed yield of 23.5 g plant −1 . The unique characteristic of this germplasm is its demonstrated improved harvest index. The release of WCL‐LO4‐Gail will benefit public and private breeders with new germplasm for variety development. It will also benefit growers and producers with the highest yielding available germplasm for production.